2019
DOI: 10.1186/s12862-018-1317-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence, population differentiation and phylogeography of the cicada Subpsaltria yangi based on molecular and acoustic data: an example of the early stage of speciation?

Abstract: BackgroundGeographical isolation combined with historical climatic fluctuations have been identified as two major factors that contribute to the formation of new species. On the other hand, biotic factors such as competition and predation are also able to drive the evolution and diversification of organisms. To determine whether geographical barriers contributed to population divergence or speciation in the rare endemic cicada Subpsaltria yangi the population differentiation, genetic structure and phylogeograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…3a). This is in line with the genetic differentiation among populations of S. yangi based on mitochondrial ( COI + COII + Cytb + A6A8 ) genes, where the mean Fst among the three comparisons, ‘HL vs HC’, ‘HL vs FX’ and ‘HC vs FX’ was 0.0735, 0.0676 and 0.0121, respectively [8]. This suggests that differential gene expression in the midgut among these populations is closely associated with genetic variations of related populations.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…3a). This is in line with the genetic differentiation among populations of S. yangi based on mitochondrial ( COI + COII + Cytb + A6A8 ) genes, where the mean Fst among the three comparisons, ‘HL vs HC’, ‘HL vs FX’ and ‘HC vs FX’ was 0.0735, 0.0676 and 0.0121, respectively [8]. This suggests that differential gene expression in the midgut among these populations is closely associated with genetic variations of related populations.…”
Section: Discussionsupporting
confidence: 76%
“…In this case, the DEGs detected in the midgut of S. yangi might be initially beneficial in the process of host shift in this species, which may subsequently evolve in a long-term feeding on a new host plant (viz., E. lepidosperma ). A previous study indicated that the HL population has evolved into a distinct independent lineage according to the analysis of population differentiation based on both molecular data and males’ calling song structure [8]. The deserts or semi-deserts surrounding the Helan Mountains were previously shown as a major dispersal and climatic barrier for gene flow of related animals [74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher degrees of genetic variation were found in both East-A ( H T = 0.843) and East-B ( H T = 0.930) lineages than in the West lineage ( H T = 0.375) ( Table 2 ), further demonstrating that population divergence in N. tangutorum originated in the eastern groups. Taken together, these data suggest that genetic variation is a major driver of population differentiation [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 98%